The Great Border Project: A Proposal to Study Torsion Energy Fields (TEF’s) in Human Beings to Explain Qi - Alton, John (The Journal of the International Society of Chinese Health Practices, 2023)
The Chinese history of Qi—loosely translatable as “vital force”— is fundamental for understanding not only traditional Chinese Medicine (TCM), but also, arguably, Chinese Civilization. However, Westerner medical and physical scientists have staunchly opposed the possibility that Qi exists. While there have been some meager studies done of Taijiquan and Qigong masters that show some ability to spontaneously regulate autonomic body functions, such as cardiovascular flow and oscillations, no Western medical researcher has shown that any Taijiquan or Qigong master can exude exceptional electromagnetic energy, beyond modest infrared radiation that others with no experience with either Taijiquan or Qigong have been able to produce. Ironically, a new Western framework for understanding and verifying Qi has emerged over the past 50 years: Torsion Energy Field (TEF). Based on proposals put forth by Albert Einstein, along with other historic physicists (e.g., Nicoli Tesla), TEF provides a plausible concept that can be used to test both modest and extravagant claims of TCM, not only in terms of human health but in environmental management (feng shui). According to theory, TEF’s are generated by spin-spin polarity of particles (electrons, protons, molecules) that become organized in inanimate objects as complex general TEF’s that become even more complex in living organisms. When set into motion, the TEF’s generated by objects and living organisms make Torsion Waves (TW’s) that propagate infinitely across spacetime and intersect with other TEF’s, thus becoming “entangled,” despite spacetime separation. The Great Border Project (GBP) is a research proposal to use one simple experimental method for TEF detection developed by Professor Konstantine Meyl, using a duel Tesla coil system and a wooden frame. With this simple design, Meyl was able to demonstrate that Tesla coils produce both left and right side TEF’s. Gao Peng (University of Science and Technology of China) successfully repeated Meyl’s original TEF detection experiment, supporting its viability as a method for TEF detection. The GBP proposes to adapt the work of Meyl and Peng to test the effect of various living organisms, in particular a human being, on the Telsa-coil-generated TEF’s. The short-term goal of the GBP is to show that the presence of living organisms will have distinct, measurable effects on TEF behavior generated by Tesla coils. The long-term goal is to show that the beating human heart with particular harmonics that have already been associated with Taijiquan and Qigong health benefits will emerge as reliable markers for TEF that relate to health and longevity. Such an outcome not only will help to explain the legitimacy of ancient traditional Chinese health practices, but may open a pathway for the development of a new scientific technology of Qi that can serve to the betterment of humankind.